Engaging Learning for Environmental Awareness: Integrating Virtual Reality in Ecological Citizenship Education - Nugroho, Dedy Ari; Wahyu, Wahyu; Casmana, Asep Rudi (Journal of Moral and Civic Education, 2025)
Virtual reality (VR) technology is increasingly being adopted in education, offering innovative and engaging methods for teaching. This study examines the application of VR-based learning media in Ecological Citizenship education, with a focus on enhancing students' environmental awareness. Through VR, students can engage in interactive simulations that realistically depict various aspects of the environment—from biological dynamics to the impacts of environmental changes. The findings demonstrate that VR not only improves students' technical understanding but also strengthens their attitudes towards environmental conservation through active participation. This research employs a qualitative approach, utilizing in-depth interviews, document analysis, and classroom observations to gather data. However, challenges at Lambung Mangkurat University, such as inadequate technological infrastructure, limited lecturer proficiency in effectively utilizing VR, and the need for curriculum-aligned content, hinder the full implementation of VR-based learning. Based on these results, the study recommends integrating VR into the curriculum as an effective pedagogical tool to foster environmental awareness and prepare future generations to be more responsive to environmental issues.